A Density Functional Theory Study on the Cobalt-Mediated Intramolecular Pauson–Khand Reaction of Enynes Containing a Vinyl Fluoride Moiety - Escorihuela, Jorge (Synthesis, 2022)
The Co2(CO)8-mediated intramolecular Pauson–Khand reaction (PKR) is an effective method for constructing polycyclic structures. Recently, our group reported a series of this type of reaction involving fluorinated enynes that proceed with reasonable reaction rates and yields. However, mechanistic studies involving these fluorinated derivatives in intramolecular PKR are scarce. In this study, density functional theory calculations are used to clarify the mechanism and reactivity of enynes containing a vinyl fluoride moiety for this reaction. In agreement with previous studies, alkene insertion is considered to be the rate-determining step for the overall Pauson–Khand reaction of enynes containing a vinyl fluoride moiety. The effect of the substituent on the Co2(CO)8-mediated intramolecular Pauson–Khand reaction has also been investigated. When introducing heteroatoms as tethering units, the fluorinated enynes exhibited lower reactivity than the malonate homologues, whereas the use of a sulfur-based tether was unsuccessful. This computational study provides detailed information about the PKR mechanism and transition-state structures, and the results are validated with previous experimental results.
Keywords: Pauson–Khand reaction; cobalt; fluorine; enynes; DFT; reaction mechanism